Idiopathic AA amyloidosis presenting with initial abdominal pain: a case report and literature review - Xia, Pianpian; Liu, Deliang; Deng, Feihong; Ou, Dalian; Deng, Mingyang (Frontiers in Medicine, 2025)
Amyloidosis is a rare disease, often secondary to chronic inflammation or autoimmune disorders, with an unclear etiology in some cases. Herein, we report a 67-year-old male patient presenting with recurrent abdominal pain and multi-system involvement. The diagnosis of AA amyloidosis was confirmed by Congo red staining of small intestinal mucosal and bone marrow biopsies. Despite comprehensive screening, no definite etiology was identified. This case highlights that amyloidosis should be considered in patients with unexplained abdominal pain and multisystem abnormalities, and early tissue biopsy is crucial for diagnosis.